Job Satisfaction Of Vocational Agriculture Teachers In The Southeastern United States - Kotrlik, Joe W.; A. P., Malek (AAAE, 1985)
Public schools continue to have difficulty retaining vocational agriculture teachers in the profession. The percentage of vocational agriculture teachers who leave the teaching profession is higher than the percentage for other teaching fields. According to Craig(1982), the turnover rate among vocational agriculture teachers was 12.9& for 1981. This rate was higher than the rate for all teachers which was estimated to be between 7% and 10% in 1980 (Relfschneider, 1980). McCracken, Smith and Suandi (1982( indicated that if county extension agents and vocational agriculture teachers are to achieve their most effective level, administrators must reduce this turnover rate.